Hubungan Penggunaan Gadget Dengan Kesehatan Mata Anak Usia Sekolah Di SD Negeri 142 Maluku Tengah - Tomasoa, Valensya Yeslin; Herwawan, Joan Herly (Lembaga Penerbitan Fakultas Kesehatan Universitas Kristen Indonesia Maluku, 2022)
Improvement in technology is the impact of the development of civilization, one of which is the existence of gadgets, which will facilitate the level of communication regardless of distance and space. For school-aged children, good eyesight is a very important factor because it supports children's learning, so that if a disturbance occurs it will hamper the child's achievement and education, thus impacting the child's achievement. For this reason, the purpose of this study was to see the relationship between the use of gadgets and the eye health of school-age children at SD Negeri 142 Central Maluku. The type of research is descriptive correlation which was conducted at SD Negeri 142 Central Maluku with a sample of 37 respondents. The sampling technique used is total sampling. The instrument used is a questionnaire). The statistical analysis used to see the relationship between the two variables is chi square. The results showed that there was a relationship between the use of gadgets and the eye health of school-age children at SD Negeri 142 Central Maluku with a p value of 0.003 (0.05).Â Keywords: Eye Health; child; Use of Gadgets.